1988
DOI: 10.1161/01.res.63.3.550
|View full text |Cite
|
Sign up to set email alerts
|

Relation between transmural deformation and local myofiber direction in canine left ventricle.

Abstract: To determine the relation between local myofiber anatomy and local deformation in the wall of the left ventricle, both three-dimensional transmural deformation and myofiber orientation were examined in the anterior free wall of seven canine left ventricles. Deformation was measured by imaging columns of implanted radiopaque markers with high-speed, biplane cineradiography (16 mm, 120 frames/sec). Hearts were fixed at end diastole and sectioned parallel to the local epicardial tangent plane to determine the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(210 citation statements)
references
References 25 publications
(34 reference statements)
13
196
1
Order By: Relevance
“…In contrast to earlier studies using uniaxial dimension gauges, we did not observe a proportionally greater reduction in deformation at the apex (16). We suspect that this is due to the difficulties with uniaxial measurements (38) at the midwall. Methoxamine infusion induced substantial and fairly uniform reduction in all strains expressed in sheet coordinates and the relative contribution of sheet strains to E 33 at each site remained uniform.…”
Section: Regional End-systolic Strains and Effects Of Afterloadcontrasting
confidence: 99%
“…In contrast to earlier studies using uniaxial dimension gauges, we did not observe a proportionally greater reduction in deformation at the apex (16). We suspect that this is due to the difficulties with uniaxial measurements (38) at the midwall. Methoxamine infusion induced substantial and fairly uniform reduction in all strains expressed in sheet coordinates and the relative contribution of sheet strains to E 33 at each site remained uniform.…”
Section: Regional End-systolic Strains and Effects Of Afterloadcontrasting
confidence: 99%
“…24,25 The technique allows precise quantification of complex 3D motion and deformation patterns, and the results correspond very well with those obtained by invasive methods that use metallic markers sewn in the myocardium. 12,26,27 Variability percentages were small and comparable with previous reports that used MR imaging to quantify LV parameters. 28 So although there is ample evidence to support the intrinsic accuracy of the technique, the limitations of the present study are introduced by the need to match MRI and PET data and the imprecision of matching serial MRI studies.…”
Section: Reliability Of Mr Myocardial Taggingsupporting
confidence: 86%
“…34, 9, 543-548 (2011) stores potential energy in both intra-and extracellular structures. 26,27 This stored energy is then released during diastolic untwisting and contributes to the formation of an intraventricular suction gradient that facilitates LV inflow. 28 -30 Numerous studies have suggested that LV Tor adaptively changes in response to ventricular loading conditions.…”
Section: Discussionmentioning
confidence: 99%